Value Added Analysis of Hanjeli Raw Materials and its Development Strategy at Pantastik Cooperative, Wado, Sumedang - Tania, Fransisca Johana; Tridakusumah, Ahmad Choibar; Ernah, Ernah (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Hanjeli (Coix lacryma-jobi L.) has potential as a high-value local food crop, yet studies on its value-added potential and business development strategies remain limited. This study aims to analyze the added value of hanjeli and formulate development strategies at Pantastik Cooperative, Wado, Sumedang. A case study approach was applied using mixed methods. The Hayami method was used to measure added value, while SWOT, IFE, EFE, and QSPM analyses were employed to formulate strategic directions. The results of the Hayami analysis show that hanjeli processing generates a value-added ratio of 66.00%, with profits predominantly accruing to the business owner, although the workforce receives a considerable share. The SWOT analysis identified that internal strengths outweigh weaknesses and external opportunities exceed threats. Based on the QSPM analysis, the most recommended strategy is to leverage healthy food trends and government support followed by expanding digital marketing. This research fills a gap in integrated analysis combining value-added assessment and strategic business formulation for underutilized crops like hanjeli. The findings imply that strengthening the value chain, increasing production capacity, and optimizing digital marketing are essential to enhance competitiveness. Effective implementation is expected to position hanjeli as a sustainable agribusiness commodity that contributes to food security, rural economic development, and the welfare of business actors.